The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1017/s0144686x16000878
|View full text |Cite
|
Sign up to set email alerts
|

‘I'm happy in my life now, I'm a positive person’: approaches to successful ageing in older adults living with HIV in Ontario, Canada

Abstract: Worldwide approximately 3.6 million people aged 50 and older are living and ageing with the human immunodeficiency virus (HIV). Few studies have explored successful ageing from the insider perspective of those living well and ageing with HIV. This study draws upon the lived experience and wisdom of older, HIV-positive adults living in Ontario, Canada in order to understand their views and strategies for successful ageing. This qualitative study involved semi-structured interviews with 30 individuals age 50 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 40 publications
0
41
0
2
Order By: Relevance
“…Living with HIV over a prolonged timeframe, often decades, increased feelings of autonomy and resiliency among midlife and older Black women. While our findings contribute to the very limited literature on resiliency, coping, and successful aging among midlife and older adults with HIV (Emlet et al 2016; Emlet, Tozay, and Raveis 2010), they also signal the need for additional research on midlife and older Black women’s experiences in navigating employment sectors and public service agencies.…”
Section: Discussionmentioning
confidence: 58%
“…Living with HIV over a prolonged timeframe, often decades, increased feelings of autonomy and resiliency among midlife and older Black women. While our findings contribute to the very limited literature on resiliency, coping, and successful aging among midlife and older adults with HIV (Emlet et al 2016; Emlet, Tozay, and Raveis 2010), they also signal the need for additional research on midlife and older Black women’s experiences in navigating employment sectors and public service agencies.…”
Section: Discussionmentioning
confidence: 58%
“…ability that enables well-being in older age" recognizing the interaction between personal and environmental factors that influence health (25). This definition moves away from the previously used term 'successful aging' and acknowledges the presence of chronic disease and resultant disability while focusing on maximizing one's function and ability within their life experience (26). However, interventions to maximize healthy aging and how to measure their impact remains less clear (25).…”
mentioning
confidence: 99%
“…However, with advances in medicine, individuals with HIV are living longer, better lives and research has started focusing on SA and SA-related factors in this population. A qualitative study in individuals with HIV (N = 30; Age range = 50-73) assessed barriers to and strategies for SA (Emlet, Harris, Furlotte, Brennan, & Pierpaoli, 2017). Results showed that while stigma, prejudice, and discrimination were identified as potential SA barriers, a number of SA-related themes emerged, including resilience components, such as self-care, mastery, and spirituality; social support; and the importance of the environmental context, such as structural support, social networks, and communities.…”
Section: Successful Aging In Individuals Living With Hivmentioning
confidence: 99%
“…Specifically, this model suggests that the environment can facilitate access to resilience-promoting resources; that resilience may differ as a result of the complex and changing nature of an individual's circumstances and the interaction with their personal traits; and that the resilience process is culturally and temporally embedded and is therefore influenced by the cultural norms of the time, which is particularly important for specific cultural groups such as minorities (Ungar, 2011). The importance of the individual-environment interaction for the well-being of disadvantaged populations can be seen in the reoccurring finding that environmental and contextual factors, such as social support and social engagement, were significant in supporting individual resilience and SA (e.g., Emlet et al, 2017;Kok et al, 2018;Scelzo et al, 2018).…”
Section: Underlying Mechanisms Of Successful Agingmentioning
confidence: 99%